We need to rewrite the equation
![F=(9C)/(5)+32](https://img.qammunity.org/2023/formulas/mathematics/college/u7lat1f3rdkga60r8cd1ulr369chblgyna.png)
isolating C on the left side of the equation.
First, we can subtract 9C/5 from both sides of the equation. We obtain:
![\begin{gathered} F-(9C)/(5)=(9C)/(5)+32-(9C)/(5) \\ \\ F-(9C)/(5)=32 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pu2lgj4t5cv4ldp0dqjtlg2pvmvv57issk.png)
Then, we can subtract F from both sides of the equation. We obtain:
![\begin{gathered} F-(9C)/(5)-F=32-F \\ \\ -(9C)/(5)=32-F \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3rg64njza5gmvitpu09tybklzqg85sxud8.png)
Then, we can multiply both sides by -5/9. We obtain:
![\begin{gathered} -(9C)/(5)\cdot(-(5)/(9))=(32-F)\cdot(-(5)/(9)) \\ \\ (-1)(-1)(9)/(9)\cdot(5)/(5)C=(32-F)\cdot(-(5)/(9)) \\ \\ C=(32-F)\cdot(-(5)/(9)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5ftwb5qyx22fpfl756bzj1461uubcrq85d.png)
Then, we can distribute the factor -5/9 over the sum 32-F on the right side:
![\begin{gathered} C=32\cdot(-(5)/(9)_{})-F\cdot(-(5)/(9)) \\ \\ C=-(160)/(9)+(5)/(9)F \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jyqpdfl875267dlxtzmpmastx4g5kkweuh.png)
Therefore, the answer can be written as
![C=-(160)/(9)+(5)/(9)F](https://img.qammunity.org/2023/formulas/mathematics/college/lwgfdl7l3pi6t3ex8o3c6watrhrowejig5.png)
Or as
![C=(5)/(9)(F-32)](https://img.qammunity.org/2023/formulas/mathematics/college/jyy6sx9ipnq2fm58cm79lkasoje3bjrlt1.png)